Recent progress on narrow-linewidth crystalline bulk Raman lasers - Quan Sheng; Hanchao Ma; Ran Li; Meng Wang; Wei Shi; Jianquan Yao (Results in Physics, 2020)
Narrow-linewidth, solid-state Raman lasers are of significant importance for numerous applications. In last decade, variety of methods have been utilized to suppress the spectral linewidth of Raman laser output. In this review we summarize the recent works of narrow-linewidth and/or single-frequency solid-state Raman lasers. The mechanisms and results are addressed while the positive and negative aspects of each technique are also discussed to give the readers a reference to choose a proper narrow-linewidth method for certain applications.